Gentiopicroside Ameliorates Sepsis-Induced Acute Lung Injury via Inhibiting Inflammatory Response - Mu Hu; Hangxiang Du; Yang Xu; Yan Wang (Canadian Respiratory Journal, 2024)
Sepsis is a systemic inflammatory reaction syndrome caused by infections. Acute lung injury (ALI) occurs first and most frequently in patients with sepsis. Gentiopicroside (GPS), which originates mostly from Gentiana, is classified as a secoiridoid glycosides. Terpenoid glycosides have various biological effects, including liver protection, blood glucose and cholesterol level management, and anti-inflammatory and antitumor effects. However, presently, the biochemical foundation and mechanism of the anti-inflammatory effects of GPS in sepsis-induced ALI have not been explained. In the present study, we established a rat model of sepsis ALI induced by cecal ligation and puncture. This enables us to observe the effects of GPS therapy, which significantly reduced the inflammatory response (TNF-α, IL-1β, and IL-6), nitrogen stress, oxidative stress, and severity of ALI at both the whole animal and molecular levels. In addition, GPS ameliorates LPS-induced ALI via regulation of inflammatory response and cell proptosis in BEAS-2B. This study provides a theoretical basis for treating sepsis-induced ALI with GPS.